Culturas oxidadoras de metano provenientes de ambientes aquáticos brasileiros e seu potencial para a produção de polihidroxialcanoatos - Soares, Juliana Aparecida Bomjardim [UNIFESP] (2018)
Microorganisms play a key role in the methane cycle. Methanogenic arches produce most of the planet's biogenic methane in anaerobic environments. Methanotrophic aerobic bacteria use methane as a source of carbon and energy, being responsible for the consumption of gas in terrestrial and aquatic environments, as well as having potential for the production of polyhydroxyalkanoates (PHA). This study aimed to study enriched metanotrophic cultures of Brazilian aquatic environments, aiming to promote and characterize the production of PHB from methane. For this, an approach was that combines dependent and independent of cultivation techniques dependent were adopted. Cultures of interest were identified by sequencing the new generation of the 16S RNAr gene on the Illumina MiSeq platform. The detection and quantification of methanotrophic indicator genes and PHA production (pmoA and phaC, respectively) were done by the PCR technique. Nile red staining and fluorescence microscopy were used as indicators of the production of polyhydroxybutyrates. The results indicated the presence of pmoA and phaC genes in all cultures analyzed. The initial Nile red assessment indicated the presence of PHAs associated with methane consumption in the cultures of interest. The sequencing results indicate the dominance of the methanotrophic genera Methylocystis (38.8% - 75%) in three of the five established cultures. One of the cultures, RB-5, was selected for a stirred vial production assay. The accumulation of polymers was quantified by means of gas chromatography. Growth curves were constructed for the determination of methanotrophic activity. The results for the production assay show a low accumulation of the poly-3-hydroxybutyrate and poly-3-hydroxyvalerate polymers by the RB-5 culture. It is expected that this work will contribute to the subsequent realization of tests aiming the optimization of polymer production by the RB-5 culture.